Trabalho intermitente: a desvalorização social do trabalho pela ruptura com a racionalidade econômico-social constitucional - Vitor, Rodrigo Ribeiro (2022)
The present research deals with intermittent work, inserted in a context of changes in labor relations driven by economic crises and ideological and social transformations resulting from the process of economic globalization, from which is moving towards increasingly intense deregulation and flexibility of labor relations. From this reality, the following research problem arises: is the intermittent work contract in the Brazilian legal system an instrument of social valorization of labor or does it only follow a rationality that contemplates economic interests, in violation of the guidelines of the Federal Constitution of 1988 itself? For this, it is assumed that the insertion of intermittent work in the Brazilian legal system is a consequence of an "opportunity" generated by the economic crisis unleashed from 2008, although the foundation has been the need for modernization of labor relations, but its regulation preponderantly contemplated the economic rationality to the detriment of economic-social constitutional rationality. With this, this research has the general objective of investigating whether the intermittent work contract in the Brazilian legal system is an instrument of social depreciation of labor, in violation of the constitutional guideline provided in art. 170 of the Federal Constitution of 1988. In turn, in order to assist in the search for this general objective, the following specific objectives were selected: a. Identify the context and the determining reasons for the transformation of labor relations and the relationship with intermittent work; b. Know the economic, social and legal reality arising from the insertion of intermittent work contract in Brazil since its implementation; c. Analyze whether the rationale underlying the regulation of intermittent work in Brazil is in line with constitutional provisions. To this end, we resort, in general, to the dialectical methodology for analysis of the economic and social perspective, also using the monographic procedure and literature review. Finally, we reach the conclusion that intermittent work is not an instrument of valorization of the worker because it is not compatible with the constitutional economic-social rationality.